"Crisis Coverage Gap": The Divide between Public Interest and Local News' Facebook Posts about COVID-19 in the United States. Issue 6 (3rd July 2022) - Masullo, Gina M.; Jennings, Jay; Stroud, Natalie Jomini
Abstract: This study sought to theorize the crisis coverage gap, a new way of understanding the divide between public information needs and local digital news coverage during a crisis, through the context of the COVID-19 pandemic of 2020. We used a three-wave panel survey of Americans ( n = 730) and analyses of local news posted on Facebook ( n = 2, 632) at three points during the early pandemic to illustrate how the crisis coverage gap operates. Findings demonstrate a clear divide between the news the public wanted about the pandemic and what local media delivered on Facebook. Specifically, the media over-delivered economic and business news relative to public interest. It left the public wanting for news about how grocery stores were responding to the pandemic and for fact cheques ascertaining the truthfulness of information about the crisis. Earlier in the pandemic, coverage of schools' responses was in line with expectations based on how interested people were, but later they were over-covered, relative to interest.